Synthesis of novel 3-(2-bromophenyl)-4-substituted-1H-1,2,4-triazole-5(4H)-thiones derivatives - A. A. Safonov; A. V. Nevmyvaka (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
A wide range of biological activity of 1,2,4-triazole derivatives (anti-inflammatory, antiviral, antitumor, immunostimulating, etc.) and the availability of sources for their preparation determine the prospects of using compounds of this class to create modified derivatives based on them and, as a result, medicines. Derivatives of 1,2,4-triazole have already established themselves both in the agricultural sector and in veterinary medicine and pharmacy.